(3TQM RHOI GdCUhds - (3eMeO HgGA GdOjf ?(B!s
(3ChdgG (B:s
(3HSe Gddg (B.. (3CHgi CUd jHfi Ydjg GdNWGH (B...(3bhdg CHgi (B: (3GdHgGA GdMSf hHGgjJg aHgjJg ZdHJg HGdMSf hHgi GdHjJ JHgjJg hqSYg , bhdg GdNWGH bO jQGO HGdNWGH GdcdGe GdehLg fMh GdZjQ dEagGeg hbO jQGO Hg eYfGg GdeUOQj (B...s
(3BNQgG (B:s
... (3hgh GKHGJ eSCdI YdejI HNHQ GdhGMO eY Cf GdeajO hZjQg WYfhG aj Jdc GdQhGjI Ke bGd aGf GMJL HCf GdeNGda ddYGeI dG jMJed EdG GdaJhi hGdehGab jMJed GdJbjI bdfG jLhR GdaJhi HeG jMJe GdJChjd (B.. (3hbY GdaQGZ(B.s
(3JGQjN JCdjag (B12 (3eMQe (B1018 (3g`s
(3JHUQI GdYfhGf (B:s
(3RHOI GdCUhd dHgGA GdOjf GdYGedjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s